2021
DOI: 10.1002/cam4.3706
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of serum inflammation indexes in different Lauren classification of gastric cancer

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…However, chemotherapy could lead to serious side effects, high drug resistance, and treatment failure (6). Interest has particularly raised toward phytochemicals and naturally occurring compounds present in dietary natural products for gastric cancer treatment purposes -thanks to low toxicity and higher tolerance rate of plant-derived phytochemicals (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…However, chemotherapy could lead to serious side effects, high drug resistance, and treatment failure (6). Interest has particularly raised toward phytochemicals and naturally occurring compounds present in dietary natural products for gastric cancer treatment purposes -thanks to low toxicity and higher tolerance rate of plant-derived phytochemicals (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…As a part of tumor immunity, the peripheral blood immune system also has a significant effect on tumor progression. Our previous studies have confirmed that the inflammatory index plays an important role in the early diagnosis of GC and the evaluation of the outcome of GC patients with different Lauren classification[ 13 , 14 ]. In addition, in liver metastases, different tumor growth pattern subtypes have different levels of lymphocyte infiltration, indicating that they have different immune states in the tumor microenvironment[ 15 ].…”
Section: Introductionmentioning
confidence: 79%
“…This evidence shows that INF can effectively help clinical experts predict the recurrence pattern and prognosis of GC patients. In addition, with the great achievements of tumor immunotherapy, it has been found that the tumor microenvironment and immune inflammatory response in peripheral blood can effectively reduce the impact of GC heterogeneity, providing more comprehensive information for the personalized treatment of patients[ 14 , 18 ]. This study was aimed at investigating the peripheral blood immune response is great value to different INF types GC patients in evaluating prognosis and individualized chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…As a complex disease that originates from the interplay between environment and host-related issues, the pathogenesis of GC is induced by many hazard factors, including Helicobacter pylori (Hp) infection, alcohol drinking, irregular diet, and genetics (2)(3)(4). The majority of GCs are adenocarcinomas, and can divided into intestinal and diffuse subtypes based on the Lauren classification system (5,6). Although traditional treatments comprise surgical resection and chemotherapy for patients with GC, their overall benefits have been limited (7).…”
Section: Introductionmentioning
confidence: 99%